NEUROLEADERSHIP AS A FACTOR IN SUCCESSFUL MANAGEMENT IN ORGANIZATIONS - Rakhmatjanov Lazizkhon Turabaevich; Alijonov Ikbol (Academia Science Repository, 2023)
In today’s world, the success of a company depends on many factors, but the main ones are human resources. A special role is played by competent and effective management of them. The article deals with the concepts of neuromanagement and neuroleadership. Neuroleadership helps to coordinate the work of company employees, taking into account the understanding of the principles of the human brain. Doing business according to the laws of neuroscience is much more difficult, since we must take into account what others think, but at the same time, the use of neuromanagement in a company helps to correct the system of staff motivation, change the relationship between managers and subordinates.